2018
DOI: 10.1002/cam4.1883
|View full text |Cite
|
Sign up to set email alerts
|

Elevated EGFL6 modulates cell metastasis and growth via AKT pathway in nasopharyngeal carcinoma

Abstract: Epidermal growth factor‐like domain multiple 6 (EGFL6) is a secreted protein, regulates maintenance and metastasis of cancer cells. Nevertheless, how EGFL6 participates in the progression and tumorigenesis of nasopharyngeal carcinoma (NPC) remains unclear. In our study, EGFL6 was detected highly expressed in 20 NPC tissues compared with normal tissues by IHC assay. Then, the level of EGFL6 in NPC serum and NPC cells was explored through enzyme‐linked immunosorbent assay and western blot, the results consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…To some extent, EGFL6 may play the same role in the process of angiogenesis no matter for tumorigenesis or SBVM, suggesting that EGFL6 could be overexpressed in SBVM and tumor. As for the level of EGFL6 in serum, two studies have reported EGFL6 level was highly expressed in nasopharyngeal carcinoma (120 pg/ ml vs. 46 pg/ml or so) [9] and oral squamous cell carcinoma (304.48 ± 194.55 pg/mL vs. 178.69 ± 102.96 pg/mL; p < 0.001) [24]. In addition, a study analyzed the serum EGFL6 levels in healthy controls and patients with various tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To some extent, EGFL6 may play the same role in the process of angiogenesis no matter for tumorigenesis or SBVM, suggesting that EGFL6 could be overexpressed in SBVM and tumor. As for the level of EGFL6 in serum, two studies have reported EGFL6 level was highly expressed in nasopharyngeal carcinoma (120 pg/ ml vs. 46 pg/ml or so) [9] and oral squamous cell carcinoma (304.48 ± 194.55 pg/mL vs. 178.69 ± 102.96 pg/mL; p < 0.001) [24]. In addition, a study analyzed the serum EGFL6 levels in healthy controls and patients with various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the structure of EGFL6 protein is more similar to Notch than EGF, which suggests that EGFL6 is functionally related to the Notch interactome [8]. To date, EGFL6 has been reported to be upregulated in many tumors such as breast, lung, and nasopharyngeal cancer [9,10] and participates in the tumor progression and metastasis. For instance, EGFL6 was recently reported to accelerate the growth and metastasis of nasopharyngeal carcinoma by regulating the expression of the Akt pathway [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies showed EGFL6 could modulate cancer cell proliferation, and metastasis in colorectal cancer and different cancer types [13,15,32,34]. In our data, knockdown EGFL6 associated with tumor cell viability reduction as well as ERK and AKT phosphorylation, indicates EGFL6 promotes CRC cells survival and proliferation through ERK and AKT pathways, this result was consistent with a research which investigated nasopharyngeal carcinoma [13]. The same result was also found in zebra sh model [37], but was different from a research in which EGFL6 recombinant protein did not change p-ERK or p-AKT level in CRC cell HCT116 and SW480 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies showed EGFL6 could modulate cancer cell proliferation, and metastasis in colorectal cancer and different cancer types [13,15,29,31]. In our data, knockdown EGFL6 associated with tumor cell viability reduction as well as ERK and AKT phosphorylation, indicates EGFL6 promotes CRC cells survival and proliferation through ERK and AKT pathways, this result was consistent with a research which investigated nasopharyngeal carcinoma [13]. The same result was also found in zebra sh model [34], but was different from a research in which EGFL6 recombinant protein did not change p-ERK or p-AKT level in CRC cell HCT116 and SW480 [15].…”
Section: Discussionmentioning
confidence: 99%